Effects of blood lactate on oxygen uptake kinetics during recovery after sprint in humans - Yano, T.; Matusura, R.; Arimitsu, T.; Yamanak, R.; Lian, C. S.; Afroundeh, R.; Kondo, S.; Yunoki, T. (Biology of Sport, 2012)
The purpose of this study was to examine the effects of blood lactate level (La) on oxygen uptake ( ·VO2) kinetics during recovery after short-term exercise with maximal effort (sprint). Three sprints were performed on a cycle ergometer with a load of 8% of body weight at maximal rotation rate. ·VO2 kinetics and oxygen debt were determined after three sprint tests: one 10-s cycling sprint, five repeated 10-s cycling sprints with 6-min intervals and one 30-s cycling sprint. There was no significant difference between peak power outputs in the 10-s sprint and five sprints. There was no difference in ·VO2 kinetics during recovery from one sprint and during recovery after five sprints. La peaked at 5 min. The peak value of La was significantly lower in one sprint (4.41 ± 0.9 mM) than in five sprints (7.01 ± 2.2 mM). Thus, despite a difference in La, there was no difference between ·VO2 kinetics during recovery after one sprint and after five sprints. There was a significant difference in ·VO2 between the five sprints and 30-s sprint from 70 s to 320 s during recovery, but there were no significant differences in La after 5 min of recovery. There were two phases in ·VO2. They consisted of fast oxygen debt and slow oxygen debt. There were also no differences in slow and fast oxygen debts between the two 10-s sprints despite significant differences in blood lactate during recovery. Peak La in the five sprints was not significantly different from that in the 30-s sprint (8.68 ± 1.2 mM). However, slow oxygen debt was significantly greater in the 30-s sprint than in the five sprints. It is concluded that ·VO2 kinetics during recovery are not affected by an increase in blood lactate.